PENJATUHAN PUTUSAN SELA TANPA ADA EKSEPSI DITINJAU DARI TUJUAN HUKUM ACARA PIDANA (Studi Putusan Sela Nomor 353/Pid.Sus/2015/PN.Sim) - Samandhohar Munthe; Alvi Syahrin; Mahmud Mulyadi; Sutiarnoto Sutiarnoto (USU LAW JOURNAL, 2019)
ABSTRACT The indictment can be declared null and void in the interim decision if there is an exception from the defendant / legal counsel. How is the position of the charges stated null and void in interlocutory decisions and the subject matter has been examined in terms of the purpose of criminal procedural law. Charges declared null and void in interlocutory decisions and have been examined the subject matter of the case is contrary to the principle of legality and Article 143 paragraph (2) letter b of the Criminal Procedure Code, causing legal uncertainty. The purpose of criminal procedure law to find material truth is not guaranteed by law. Material requirements must not be too broad and broad, enough careful, concise, clear, and complete description of the time and place of the crime. The interim verdict stated that the invalidation of law without an exception did not fulfill the principle of legal certainty in accordance with Article 156 paragraph (1) and paragraph (2) of the Criminal Procedure Code. Witness information is not a material requirement in Article 143 paragraph (2) letter b of The Criminal Procedure Code.  In order for the indictment to be declared null and void in the interlocutory verdict and to have examined the subject matter of the case, it must be dropped in the final decision. In order for the purpose of criminal procedural law to seek material truth, it is stated in the law. In order for the judge to make the final verdict, the witness who was not questioned by the investigator was included as things that burdened the defendant.   Keywords: Interim Decision, Indictment, Indictment Canceled For Law, Without Exception, Examination of Case Principles.